Design and development of café management system - Loh, Zhan Hong (2024)
The growing demand for efficiency in the food and beverage sector, especially within cafes, is the driving force behind the development of a Café Management System. This initiative is motivated by several factors. Firstly, the industry has seen significant expansion due to evolving consumer preferences and lifestyles, making cafes popular venues for socializing, working, and relaxing. Secondly, managing café operations involves many complex tasks, such as order processing and inventory control, which can be challenging to handle effectively. The traditional method of paper-based record-keeping requires substantial resources in terms of labour, time, and cost, making it less efficient compared to a digital management system. While existing management systems exist, there is still space for improvement. Therefore, this project aims to enhance the current system by creating a more efficient solution, The Café Management System is designed to streamline operations, enhance customer experience, and provide data-driven insights to support informed decision-making, these objectives align with broader industry trends toward digitalization and sustainability in the food and beverage sector.